ANALISIS BRAND PERCEIVED QUALITY ICE CREAM BARCELONA DI KOTA PEKANBARU - Ika Wijayanti; Sri Restuti; Tengku Firli Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to determine the perceived quality/Brand Perceived Quality (BPQ) ice cream Barcelona in Pekanbaru The population in this study is that consumers who live in the city of Pekanbaru and never consume ice cream Barcelona. Minimum of respondents who used the respondents was 96.04, the number of respondents in this study used is rounded to 100 respondents. The analysis technique used in this study is the Importance Performance Analysis or analysis of perceived quality / Brand Perceived Quality (BPQ). Based on the results of the study of consumer perceptions of products Ice Cream Barcelona in Pekanbaru is low this can be seen from each of the respondents is not biased to meet consumer expectations of what is expected by the consumer. The variable that has the greatest degree of satisfaction is Benefit then packaging, followed by Product and Warranty.Keywords: Perceived Quality Brand